Disputes for the Representation of the Indigenous Body on Twitter - Bonin, Iara Tatiana; Kirchof, Edgar Roberto; Ripoll (Universidade Luterana do Brasil – ULBRA, Canoas/RS, Brazil), Daniela (Revista Brasileira de Estudos da Presença, 2022)
The paper aims to analyze the representations of the indigenous body produced during the 14th edition of the Acampamento Terra Livre [Free Land Occupation], which happened between April 24th and 28th, 2017, and that were disseminated and debated by means of images and threads in the social network Twitter from then on. The analyses are situated within the Cultural Studies field and the results point, on one hand, to a representation that considers the generic identity of the indigenous as a strategy to confer visibility to their social and political demands and, on the other, for disputes and clashes around these same representations.